Assessing the Influence of Mobile-Assisted Language Learning on English Proficiency Among ELT Students - Dewi, Oktavia Tri Sanggala; Mukminatien, Nur; Ivone, Francisca Maria; Wulyani, Anik Nunuk (Journal of Teaching and Learning, 2026)
This study investigates the impact of mobile-assisted language learning (MALL) on the English proficiency of English language teaching (ELT) students, comparing its effectiveness to traditional classroom-based instruction. A quasi-experimental design was employed, with 32 ELT students assigned to either an experimental group using commercial learning platforms (CLPs) or a control group receiving traditional instruction over the semester. The results indicated that, based on pre- and post-test scores, the experimental group achieved significantly greater improvements in overall English proficiency compared to the control group. Specifically, the experimental group exhibited greater improvements across all language skills, including vocabulary, listening, speaking, and reading. In addition, students in the MALL group expressed positive perceptions of the platforms, emphasizing increased engagement, flexibility, and motivation, which contributed to enhanced learning experiences. Students also highlighted challenges, such as technical issues and repetitive exercises, but overall, they favoured integrating MALL into their learning routines. These findings suggest that MALL can effectively enhance comprehensive language proficiency and that ELT students view it as a valuable tool for language learning. This study underscores the potential of MALL to improve language outcomes and provides insights into students’ attitudes towards its integration into language education.